Analisis Gaya Kepemimpinan, Kompetensi, Kepuasan Kerja terhadap Kinerja melalui Budaya Organisasi, Motivasi Kerja sebagai Pemoderasi - Gatot Basuki HM; Bagas Agung Pranata (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
PT. Jago Rental is a heavy equipment rental company that provides a variety of heavy equipment such as: Excavators, Bulldozers, Vibro and others. The company's income only depends on the way employees market their products. Often companies experience losses, due to reduced company turnover each year. This is due to factors from the performance of employees who are less enthusiastic in carrying out their duties. Based on this background, this study aims to determine the factors that significantly influence the development of employee performance, namely: leadership style, employee competence, job satisfaction, organizational culture and work motivation. In this study using the Structural Equation Modeling (SEM) method with Moderate Regression Analysis (MRA) which was processed using Smart PLS. The results of this study show that leadership style (0.035), employee competence (0.040), job satisfaction (0.010) have a significant effect (α=0.05) on employee performance. Meanwhile, organizational culture variables were able to moderate and have a significant effect between job satisfaction (0.006) on employee performance, but were not able to strengthen the relationship between leadership style (0.071), employee competence (0.458) on employee performance. For work motivation variables were able to moderate the relationship between leadership style (0.011), job satisfaction (0.011) to employee performance, but were not able to strengthen the relationship between employee competence (0.778) to employee performance.